Peran Bauran Pemasaran Terhadap Keputusan Pembelian Generasi Milenial: Studi Jajanan Tradisional - Ira Mayasari; Novita Widyastuti Sugeng; Heny Ratnaningtyas (Islamic University of Kalimantan MAB Banjarmasin, 2021)
This study aims to analyze the effect of the marketing mix of traditional snacks on purchasing decisions. The research method uses multiple regression analysis. The population in this study is the millennial generation in Jakarta. While the sample amounted to 114 respondents. The results of the research partially all the variables of the marketing mix of traditional snacks consisting of product, price, place, promotion, physical facilities, people and processes have a significant effect on purchasing decisions. To reach a large market, traditional snacks must be followed by: (1) Good product quality includes appearance, variety, taste and texture; (2) Price affordability; (3) a strategic place to sell traditional snacks such as in traditional markets, cake shops, school canteens, and food stalls near homes; (4) Advertise traditional snacks on Instagram, Facebook and Twitter; (5) The cleanliness of the place to sell traditional snacks must be paid more attention (6) The service quality of people who sell traditional jayanan products must be better; (7) The processing of traditional snacks is modern so it takes a long time. The suggestion from this research is that the promotion of traditional snacks should be improved, especially in developing social media and traditional snacks innovations.Keywords: Product, Price, Place, Promotion, Physical Facilities, People, Process, Purchase Decision